Analisis Dampak DPK dan Pembiayaan terhadap Produktivitas Pengelolaan Dana Sosial Pada Bank Umum Syariah - Lisnawati Lisnawati; Ruhadi Ruhadi; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Sharia bank has a function as a tamwil and baitul mal institution. This research aims to determine the influence of third-party funds and the financing channeled towards the receipt of social funds. In addition, this research also aims to find out the productivity of sharia banking in managing social funds using the DEA method with the Malmquist Index. Purposive sampling was used to collect data in this study. Based on the results of this study found that financing has a positive influence on the receipt of social funds, but third party funds have a negative influence on the receipt of social funds. Furthermore, based on the Malmquist Index found that 4 Syariah Banks experienced an increase in the productivity of social fund management while the other 3 Syariah Banks experienced a decrease in the productivity of social fund management, resulting from sharia banking's ability to use technology and information also the management improvements.